Low pressure amide hydrogenation enabled by magnetocatalysis - Sheng-Hsiang Lin; Sihana Ahmedi; Aaron Kretschmer; Carlotta Campalani; Yves Kayser; Liqun Kang; Serena DeBeer; Walter Leitner; Alexis Bordet (Nature Communications)
Abstract The catalytic hydrogenation of amides with molecular hydrogen (H2) is an appealing route for the synthesis of valuable amines entering in the preparation of countless organic compounds. Running effective amide hydrogenation under mild H2 pressures is challenging although desirable to preclude the need for specialized high-pressure technologies in research and industry. Here we show that magnetocatalysis with standard supported catalysts enables unprecedented amide hydrogenation at mild conditions. Widely available and commercial platinum on alumina (Pt/Al2O3) was functionalized with iron carbide nanoparticles (ICNPs) to allow for localized and rapid magnetic induction heating resulting in the activation of neighboring Pt sites by thermal energy transfer. Exposure of the ICNPs@Pt/Al2O3 catalyst to an alternating current magnetic field enables highly active and selective hydrogenation of a range of amides at a reactor temperature of 150 °C under 3 bar or even ambient pressure of H2. ICNPs@Pt/Al2O3 reacts adaptively to fluctuations in electricity supply mimicking the use of intermittent renewable energy sources. This work may pave the way toward a greatly enhanced practicability of amide hydrogenation at the laboratory and production scales, and demonstrates more generally the broad potential of the emerging field of magnetocatalysis for synthetic chemistry.